Laser-activated irrigation: Cavitation and streaming effects from dental lasers - Anton y Otero, Clara Isabel; Marger, Laurine; Di Bella, Enrico; Feilzer, Albert; Krejci, Ivo (Frontiers in Dental Medicine, 2023)
This study aimed to assess the generation of laser-induced agitation (LIA) with a 9300nm CO2 laser (Solea, Convergent Dental, USA), a 455nm and 970nm diode laser (SIROLASE, Dentsply Sirona Deutschland GmbH, Bensheim, Germany) as well as a 810nm and a 980nm diode lasers (Wiser Doctor Smile 808nm and 980nm, Lambda SpA, Brendola, Italy) with and without carbon coated “hot-tips” for improved irrigation in endodontics. Therefore the formation of cavitation bubbles at the laser tip-ends in different liquids was evaluated and compared to the traditionally applied Er:YAG laser (LiteTouch, Light Instruments, Israel). The CO2 laser was applied at different power settings at 14Hz repetition rate, SIROLASE for each wavelength at 10% Duty Cycle and WISER with both wavelengths at different power settings and wavelengths. LAI was videotaped with a high-speed camera (Redlake, MotionXtra HG-100K, Videal, Serial No. 150176). To measure the streaming velocity due to cavitation, all lasers were loosely coated with carbon particles and activated in pure water. The, due to LAI, moving particles has been videotaped with the same high-speed camera set-up. To determine the streaming velocities, the movement of one carbon particle was tracked with the help of a measuring tool in ImageJP software (ImageJ 1.52k, Wayne Rasband, National Institutes of Health, USA) and streaming velocities were calculated. With both diode laser devices at four wavelengths, it was only possible to introduce clear cavitation bubbles with low power parameters (180mW for the SIROLASE and 200mW average power for the WISER laser). With black coating of the laser tips, 9300nm CO2 laser produced clear cavitation bubbles with all tested parameters. Consequently, all tested lasers produced streaming of the liquid, with decreasing velocities at increasing distances from the laser tip: Er:YAG laser 6.4m/s, CO2 laser up to 5m/s and diode lasers between 0.01-0.09m/s. LAI with Er:YAG and 9300nm CO2 laser generated high and similar streaming velocities. The diode lasers tested generated significantly lower streaming velocities.